Cloning, Expression, and Purification of Recombinant Lysostaphin From Staphylococcus simulans - Farhangnia, Leila (Kowsar, 2014)
BACKGROUND: Staphylococcus aureus is one of the most common causes of nosocomial infections and its resistance to antibiotics is a global concern. Lysostaphin is an antimicrobial agent belonging to a major class of antimicrobial peptides and proteins known as the bacteriocins. It exhibits a high degree of anti-staphylococcal bacteriolytic activity. OBJECTIVES: In this study, high level of recombinant mature lysostaphin in Escherichia coli was produced by using pET32a expression vector. MATERIALS AND METHODS: The S. simulans gene encoding lysostaphin was extracted, amplified by polymerase chain reaction (PCR), and sub-cloned in prokaryotic expression vector pET32a. E. coli BL21 (DE3) plysS were transformed with pET32a-lys and gene expression was induced by IPTG. The expressed protein was purified by affinity-chromatography using (Ni-NTA) resin. RESULTS: PCR and sequencing results confirmed the successful cloning of the target gene into the vector. The expression of protein was induced by IPTG and high concentration of the recombinant protein was obtained via the purification process by affinity-chromatography. CONCLUSIONS: Our data showed that the recombinant mature lysostaphin protein produced by pET32a vector in E. coli system was very efficient.